Peer Group and Family Background as Correlates of Indiscipline among Adolescent Students in Ovia North East LGA of Edo State, Nigeria - Ahanor, Festus Osasumwen; Omoregbe, Iyore Ivy (NIU Journal of Social Sciences; Vol 9 No 3 (2023): NIU Journal of Social Sciences, Vol. 9 No. 3, September 2023DO - 10.58709/niujss.v9i3.1716, 2023)
The study assessed peer group and family background as correlates of indiscipline among adolescent students in Ovia North East Local Government Area. The study adopted the descriptive survey with the correlational approach design and the questionnaire was the instrument used for collecting data from a sample of two hundred and seventy (270) students who were randomly selected from nine secondary schools in Ovia North East Local Government Area of Edo State. Two research questions were raised and their corresponding hypotheses were also formulated to guide the study and tested at.05 level of significance. The reliability obtained had an r value of 0.78. The data collected were analyzed using Pearson Product Moment Correlation Co-efficient formula. The results revealed that peer group influence and family background significantly influences indiscipline among adolescent students. Based on the findings, it was recommended among others that since the primary upbringing of children lies with parents and one of the significant factors that promulgates indiscipline are family background; thus, parents should always inculcating the right moral values in their children by conforming to societal norm themselves so that they will not influence their wards negatively. Keyword: Peer Group, Family Background, Indiscipline, Adolescent